Supporting Job Search for Mauritian Youth with Little Education - Castaneda, Jorge Luis (World Bank, Washington, DC, 2020)
Boosting shared prosperity also means including disadvantaged groups in the labor market. While many factors can hinder labor force participation, behavioral factors have emerged as key barriers in the case of Mauritian youth with little education. This Note describes the results of an intervention that delivered training on job search, goal setting, and planning skills to a group of young job-seekers with low educational attainment in Mauritius. While the intervention had to be interrupted due to the COVID-19 outbreak, preliminary results show encouraging positive impacts for youth employability and job search behaviors, and point to useful lessons.